Impact of Increasing and Falling Banking Stock Prices in Indonesia 2017–2022 - Faisal, Yusuf; Sari, Egi Gumala (Economics and Business Solutions Journal, 2024)
This study aims to determine the effect of the Current Ratio, debt-to-equity ratio, Return on Assets, and Inflation on Stock Price.This research uses quantitative data; the sample in this study is stock price banks sub-sector companies that are listed on the Indonesia Stock Exchange in the period 2017-2022, with as many as 25 companies. The analysis technique used to test the hypothesis is multiple regression analysis using Eviews9 software.The results of this study indicate that the current ratio variable has a positive and statistically insignificant effect on stock price, the debt-to-equity ratio variable has a positive and statistically insignificant effect on stock price, the return on assets variable has a positive and statistically significant effect on stock price, the inflation variable has a positive and statistically insignificant effect on stock price. This research hopes to provide information regarding how stock prices can benefit decision-making and can be used as reference material for further research